2004
DOI: 10.1016/j.jsgi.2003.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Alpha-Fetoprotein, Insulin-Like Growth Factor Binding Protein-3, c-erbB-2, and Epidermal Growth Factor in Serum of Patients With Endometriosis

Abstract: Although AFP, IGFBP-3, c-erbB-2, and EGF are not altered in the circulation of patients with endometriosis, their involvement in the development of endometriotic lesions cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…IL1 and IL6) that induce the synthesis of CRP have suppressive effects on the synthesis of albumin and AFP, it could be hypothesized in this study that insignificant change in the level of AFP observed in this study may be associated with increased level of CRP observed in the leiomyoma patients. This study seems to agree with the report by Philippoussis et al (2004) that patients with endometriosis did not show significant change in the serum level of AFP.…”
Section: Discussionsupporting
confidence: 93%
“…IL1 and IL6) that induce the synthesis of CRP have suppressive effects on the synthesis of albumin and AFP, it could be hypothesized in this study that insignificant change in the level of AFP observed in this study may be associated with increased level of CRP observed in the leiomyoma patients. This study seems to agree with the report by Philippoussis et al (2004) that patients with endometriosis did not show significant change in the serum level of AFP.…”
Section: Discussionsupporting
confidence: 93%
“…EGF is a single polypeptide chain of 53 amino acid residues and plays a role in many processes such as DNA synthesis, mitogenesis, and proliferation of many cell types, including endometrial cells (44). Previous studies have found no difference in levels of EGF receptor between women with and without endometriosis (16), and serum levels of EGF itself were not found to correlate with the disease (45). Results obtained from our research are in accordance, with similar serum levels of EGF between patients with endometriosis and controls.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1 levels in eutopic endometrium are lower in severe endometriosis (185), whereas ectopic endometrium and peritoneal fluids show higher levels (186,187). There was no association found, however, between serum levels of IGFBP-3, alpha-fetoprotein (AFP) and EGF and the existence of endometriosis (188).…”
Section: Angiogenic-and Growth Factorsmentioning
confidence: 93%